National scientific and practice conference “Topical issues of nursing science and practice, 2017” - Center of Excellence of Healthcare and Pharmacy Specialists informs, (Slauga. Mokslas ir praktika, 2020)
National scientific and practice conference “Topical issues of nursing science and practice, 2017”